Efficient chirality transfer from chiral amines to oligo(p-phenylenevinylene)s to fabricate chiroptical materials. Issue 22 (27th May 2022) - Ma, Mingfang; wang, Bo; Hao, Aiyou; Xing, Pengyao
Abstract : The coassembly of OPV luminophores into chiral assemblies with tunable optical activity, showing potential for chiroptical application in optical chirality sensing. Abstract : Oligo( p -phenylenevinylene) (OPV)-based luminophores show versatile luminescence properties based on their structural and packing arrangements, and however have seldomly been utilized in fabricating chiroptical materials. Here, we report a co-assembly strategy to introduce hydrophilic chiral amines into OPV-appended carboxylic acids via salt-bridge type hydrogen bonds. The coassembly in aqueous media allows for efficient chirality transfer with chiroptical activities. The participation of chiral amines altered the aromatic stacking from H- to J-type, which greatly enhanced the luminescence of the OPV compounds and facilitated the emergence of Cotton effects as well as circularly polarized luminescence. This work demonstrates the successful coassembly of OPV luminophores into chiral assemblies with tunable optical activity, showing potential for chiroptical application in optical chirality sensing.